Knowledge, skills and attitudes of hospital pharmacists in the use of information technology and electronic tools to support clinical practice: A Brazilian survey - Néri, Eugenie Desirèe Rabelo; Meira, Assuero Silva; Vasconcelos, Hemerson Bruno da Silva; Woods, David John; Fonteles, Marta Maria de França (PloS one, 2017)
This study aimed to identify the knowledge, skills and attitudes of Brazilian hospital pharmacists in the use of information technology and electronic tools to support clinical practice. A questionnaire was sent by email to clinical pharmacists working public and private hospitals in Brazil. The instrument was validated using the method of Polit and Beck to determine the content validity index. Data (n = 348) were analyzed using descriptive statistics, Pearson's Chi-square test and Gamma correlation tests. Pharmacists had 1-4 electronic devices for personal use, mainly smartphones (84.8%; n = 295) and laptops (81.6%; n = 284). At work, pharmacists had access to a computer (89.4%; n = 311), mostly connected to the internet (83.9%; n = 292). They felt competent (very capable/capable) searching for a web page/web site on a specific subject (100%; n = 348), downloading files (99.7%; n = 347), using spreadsheets (90.2%; n = 314), searching using MeSH terms in PubMed (97.4%; n = 339) and general searching for articles in bibliographic databases (such as Medline/PubMed: 93.4%; n = 325). Pharmacists did not feel competent in using statistical analysis software (somewhat capable/incapable: 78.4%; n = 273). Most pharmacists reported that they had not received formal education to perform most of these actions except searching using MeSH terms. Access to bibliographic databases was available in Brazilian hospitals, however, most pharmacists (78.7%; n = 274) reported daily use of a non-specific search engine such as Google. This result may reflect the lack of formal knowledge and training in the use of bibliographic databases and difficulty with the English language. The need to expand knowledge about information search tools was recognized by most pharmacists in clinical practice in Brazil, especially those with less time dedicated exclusively to clinical activity (Chi-square, p = 0.006). These results will assist in defining minimal competencies for the training of pharmacists in the field of information technology to support clinical practice. Knowledge and skill gaps are evident in the use of bibliographic databases, spreadsheets and statistical tools.